IMPLEMENTASI API TELEGRAM SEBAGAI ANTARMUKA MANUSIA-MESIN UNTUK SISTEM MONITORING DAN NOTIFIKASI KONDISI REAL-TIME INFRASTRUKTUR PUBLIK - Joni Wijaya Fathoni; Ngurah Indra ER; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2025)
Public Street Lighting (PJU) is a crucial component of public infrastructure, but ineffective real-time maintenance often leads to slow damage detection, resulting in energy waste, high maintenance costs, and increased safety risks. Previous research has highlighted the importance of proactive monitoring systems based on the Internet of Things (IoT) for PJU energy efficiency. However, conventional Human-Machine Interface (HMI) solutions such as custom mobile applications are often expensive and inflexible. This research proposes the implementation of the Telegram API as a low-cost HMI for a real-time monitoring and damage notification system for PJU. This system integrates an ESP32 microcontroller with an LDR sensor, ultrasonic sensor, and PZEM-004T module for acquiring data on light intensity, traffic activity, and electricity consumption. The Telegram Bot is utilized to send monitoring data and damage notifications in real-time to operators without requiring additional applications or dedicated servers. The main innovation lies in using Telegram as the primary communication medium, which is fast, secure, and efficient. Test results show that the system successfully detects and notifies light conditions and monitors energy consumption accurately, with notifications received within 1-2 seconds as long as the internet connection is stable. This implementation proves that the Telegram API is a functional, responsive, secure, and cost-effective HMI solution for public infrastructure management, offering flexibility and ease of access across various platforms.